Verbeelding en hoop by Walter Brueggemann en die terapeutiese benutting daarvan - H.C. van Zyl; J.C. Muller (Hervormde teologiese studies, 2002)
Walter Brueggemann on imagination and hope applied to therapeutic practice Imagination and hope are two key concepts in the theology of Walter Brueggemann, an Old Testament scholar. Prophetic texts from the Old Testament, analysed by Brueggemann, are discussed in this article. The principles derived from the texts – focussing primarily on imagination and hope – are applied to the therapeutic practice under the headings (1)general principles concerning the narrative therapy, (2)language and metaphors and (3)suffering and grief.